Functional activity changes after vergence and accommodative rehabilitation of concussion-related convergence insufficiency: CONCUSS clinical trial fMRI results - Sangoi, Ayushi; Hajebrahimi, Farzin; Gohel, Suril; Scheiman, Mitchell; Goodman, Arlene; Noble, Melissa; Alvarez, Tara L. (Frontiers in Neuroscience, 2025)
IntroductionThe CONCUSS clinical trial examined the neural changes associated with office-based vergence/accommodative therapy with movement (OBVAM) in concussion-related convergence insufficiency (CONC-CI).MethodsThe following assessments were collected at baseline and post-OBVAM therapy: activity evoked from a functional MRI vergence oculomotor task, near point of convergence (NPC), positive fusional vergence (PFV), vergence facility (VF), and visual symptoms from a sensorimotor vision exam. Fifty-four CONC-CI participants, diagnosed with persisting concussion symptoms between one- and six-months post-injury, were analyzed in group-level results.ResultsFunctional activity in the vergence oculomotor network, specifically the frontal eye fields, supplemental eye fields, parietal eye fields, cerebellar vermis (CV), and visual cortex, increased post-OBVAM compared to baseline assessments. Significant increases in post-OBVAM compared to baseline assessments were observed in the visual cortex (bilateral V3 and right area PH) and the CV, via a paired t-test with family-wise error corrected for multiple comparisons (p < 0.05). The pooled baseline and post-OBVAM measures revealed that the bilateral functional activities of V3 and CV were significantly correlated with the NPC, PFV, and VF clinical signs, and the right hemisphere area PH within the visual cortex was significantly correlated with VF (Bonferroni-corrected; p < 0.001). To determine whether the CONC-CI post-OBVAM functional brain activity differed from that of the binocularly normal control (BNC) data, an unpaired t-test was performed comparing 46 age-matched BNC datasets with 54 CONC-CI datasets. Significant differences in functional activity between BNC and CONC-CI at post-OBVAM datasets were not observed (p > 0.05).DiscussionResults support that OBVAM improves functional brain activity in CONC-CI correlated with NPC, PFV, and VF.